Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinrja Pegawai (Studi Kasus di Kantor BP3AKB) - Yuliyanti, Artikha Dwi (2016)
The research objective is to analyze the influence of motivation on employee performance BP3AKB, analyze the effect of labor discipline BP3AKB to employee performance, and analyze the influence of motivation and disciplkine of employees working together on employee performance BP3AKB Boyolali. This research is a quantitative descriptive study, the study population is all employees BP3AKB Boyolali districts totaling 100 people, the study sample was taken 50 samples of peoples with simple random samplimg technique. Methods of data analysis using Test instruments include, validity and reliability, Test hypotheses, including multiple linear regression test, F test, t Test and the coefficient of determination, Test classic assumptions, including normality test, multicollinearity, hereroscedasticity. Motivation result showed a positive and significant effect on empolyee performance, discipline working positive and significant impact on employee performance, work motivation and work discipline positive and significant impact together on the performance of employees in the Office of BP3AKb Boyolali.